2013
DOI: 10.1002/mma.2785
|View full text |Cite
|
Sign up to set email alerts
|

Spatial‐skin effect for eigenvibrations of a thick cascade junction with ‘heavy’ concentrated masses

Abstract: A spectral problem for the Laplace operator in a thick cascade junction with concentrated masses is considered. This cascade junction consists of the junction's body and a great number 5N=O(ϵ−1) of ϵ‐alternating thin rods belonging to two classes. One class consists of rods of finite length, and the second one consists of rods of small length of order scriptOMathClass-open(ϵMathClass-close). The density of the junction is of order O(ϵ−α) on the rods from the second class and scriptOMathClass-open(1MathClass-cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Such successful applications of thick-junction constructions have stimulated active learning BVP's in thick junctions with more complex structures: thick junctions with the thin junction's body [2,3,4], thick multi-level junctions [8,9,18], thick cascade junctions [5,17], where new qualitative results were obtained. Specifically, it was shown that processes in thick multi-level junctions behave as a many-phase system and thick cascade junctions have new kind of eigenvibrations.…”
mentioning
confidence: 99%
“…Such successful applications of thick-junction constructions have stimulated active learning BVP's in thick junctions with more complex structures: thick junctions with the thin junction's body [2,3,4], thick multi-level junctions [8,9,18], thick cascade junctions [5,17], where new qualitative results were obtained. Specifically, it was shown that processes in thick multi-level junctions behave as a many-phase system and thick cascade junctions have new kind of eigenvibrations.…”
mentioning
confidence: 99%
“…Let us verify the solvability condition (27) for the problem (24) at any fixed k ∈ N, k ≥ 2 . Taking into account the third relation in problems (9), (11) and (13), the equality (27) can be re-written as follows:…”
Section: Limit Problem and Problems For {ω K }mentioning
confidence: 99%
“…Homogenization of oscillating boundaries with fixed amplitude is widely studied and we refer to the following main papers: [1], [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13], [15], [21], [22], [23], [24], [26], [27], [28], [29], [30], [31], [32], [41] [42], [45], [46], [47], [48], and [53].…”
Section: Introductionmentioning
confidence: 99%